2019
DOI: 10.1097/md.0000000000014816
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis interval and its association with emergency care and mortality

Abstract: End-stage renal disease (ESRD) incidence in Taiwan is highest worldwide. This study analyzed the relationship between health resource use and patients on hemodialysis (HD) asking for medical help as well as the outcomes in Taiwan.This was a retrospective cohort study that analyzed the medical data of patients on dialysis, which were collected from the National Health Insurance Database of Taiwan for the period 2000 to 2010. The study sample was screened out, and new patients starting HD from 2001 to 2005 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…DN is caused by long-term abnormal glucose metabolism, which results in decreased glomerular filtration rate and glomerular sclerosis, and thus leads to damage to renal functions, causing great harm to the health of patients [ 11 ]. At present, maintenance hemodialysis can be used to effectively prolong the survival time of patients; however, long-term hemodialysis leads to the occurrence of cardiovascular and cerebrovascular events and increases the risk of death [ 12 ]. In this study, the incidence of cardiovascular and cerebrovascular events in 144 patients with DN receiving maintenance hemodialysis was 43.75%, which is basically consistent with the results of Mei et al [ 13 ] and Luo et al [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…DN is caused by long-term abnormal glucose metabolism, which results in decreased glomerular filtration rate and glomerular sclerosis, and thus leads to damage to renal functions, causing great harm to the health of patients [ 11 ]. At present, maintenance hemodialysis can be used to effectively prolong the survival time of patients; however, long-term hemodialysis leads to the occurrence of cardiovascular and cerebrovascular events and increases the risk of death [ 12 ]. In this study, the incidence of cardiovascular and cerebrovascular events in 144 patients with DN receiving maintenance hemodialysis was 43.75%, which is basically consistent with the results of Mei et al [ 13 ] and Luo et al [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-one percent (689 of 1351) of ED encounters for an ACSC resulted in a hospital admission compared with 28.8% (9396 of 32 678) for a non-ACSC-related ED encounter (P < .001). Hospital length of stay was slightly shorter for ACSC-related ED encounters resulting in admission than for non-ACSC-related admissions (median [IQR], (5 [3-9] days vs 7 [4][5][6][7][8][9][10][11][12][13][14][15] days). Differences in the top 10 diagnoses most responsible for the ED encounter (patient-and encounter-level analyses) for the first ED encounter and any ED encounter stratified by ACSC status are provided in eTables 2 and 3 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…People with kidney failure receive emergency care for a variety of health issues that occur both with and as a result of their underlying kidney disease . Studies have noted temporal trends in increased acute care use during specific periods, such as after long interdialytic intervals and shortly before and after initiating dialysis . However, the medical reasons prompting ED visits are broadly distributed across many diagnoses that can be but are not necessarily related to kidney failure or the need for dialysis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our results, admission was predominantly on Monday and Tuesday with a long interval between last hemodialysis and admission. Chien et al reported that patients with regular hemodialysis schedules on Monday–Wednesday–Friday needed emergency treatment most frequently on Mondays, whereas those with schedules on Tuesday–Thursday–Saturday needed it most frequently on Tuesdays [8]. A total of 48 (40.7%) in 118 events were observed on Mondays and Tuesdays in their report.…”
Section: Discussionmentioning
confidence: 99%